2017
DOI: 10.7861/clinmedicine.17-3-251
|View full text |Cite
|
Sign up to set email alerts
|

Medical problems in pregnancy

Abstract: The prevalence of medical problems in pregnancy is increasing because of a complex interplay between demographic and lifestyle factors, and developments in modern medicine. Maternal mortality and morbidity resulting from treatable medical conditions, such as venous thromboembolism, epilepsy and autoimmune disease, have not decreased in recent years. This is despite a marked decrease in overall maternal mortality. It is vital that all physicians acquire a basic knowledge and understanding of medical problems in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Pregnancy is a physiological process that entails several multisystem changes [ 1 ]. Pathological conditions may appear during pregnancy such as Urinary tract infections (UTIs), pre-eclampsia, and gestational diabetes [ 2 ]. Few reports have been conducted to date to assess the impact of lower urinary tract symptoms (LUTS) during pregnancy [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy is a physiological process that entails several multisystem changes [ 1 ]. Pathological conditions may appear during pregnancy such as Urinary tract infections (UTIs), pre-eclampsia, and gestational diabetes [ 2 ]. Few reports have been conducted to date to assess the impact of lower urinary tract symptoms (LUTS) during pregnancy [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-operatively all patients were admitted to private rooms in a postpartum floor with no Covid-19 positive patients or patients under investigation. The rates of medical comorbidities including obesity, hypertension, diabetes, and asthma were representative of our typical patient population 16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…A study performed in Cameroon indicated that the consumption of medications is higher among pregnant women with health problems (Leke et al, 2018). Regarding the use of safe medications, this may have been driven by a need for pharmacological treatment (Nordeng et al, 2001), confirming once again the importance of monitoring pregnant women to ensure adequate treatment of their chronic or acute pathologies (Narayan & Nelson-Piercy, 2017;Osorio-de-Castro et al, 2004).…”
Section: Discussionmentioning
confidence: 99%